The Influence of Social Environment, Peers, and Reward and Punishment Systems on Student Discipline - Yudha Pratama Nasution; Muhammad Fadhli (Journal of Educational Management Research, 2026)
This study aims to examine the influence of the social environment, peer groups, and the reward and punishment system on student discipline. A quantitative approach with an ex post facto research design was employed to investigate the relationships among the variables. Data were collected through structured questionnaires administered to students and analyzed using validity and reliability testing, classical assumption tests, multiple linear regression, partial significance (t-test), simultaneous significance (F-test), and the coefficient of determination (R²). The results demonstrate that the social environment, peer groups, and the reward and punishment system each have a positive and statistically significant influence on student discipline, both individually and collectively. Among these factors, a supportive social environment and constructive peer interactions strengthen students’ adherence to school rules, while the consistent implementation of a fair reward and punishment system reinforces disciplined behavior. These findings suggest that student discipline is shaped not only by individual factors but also by external social and institutional influences. The study implies that schools should establish collaborative partnerships with families and the wider community while implementing consistent disciplinary policies to create a positive educational environment that promotes sustainable disciplinary behavior and supports students’ character development.